Exploring State Audit Integrity: Media Insights into Bribery During Financial Examinations - Siahay , Adolf Z. D.; Salle, Agustinus (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This article explores the phenomenon of bribery in the financial examination process conducted by Indonesia’s Supreme Audit Institution (BPK) using media-based content analysis. Drawing on reported cases from 2020 to 2025—this study identifies patterns in motives, actors, methods, and impacts of bribery in audit practices. The study uses qualitative content analysis and applies the Fraud Triangle, Agency Theory, and Klitgaard’s Corruption Formula as analytical frameworks. Findings indicate that bribery is often motivated by the desire to secure a favorable audit opinion (WTP) or to conceal financial irregularities, facilitated through informal transactions involving both public officials and auditors. The study concludes that bribery in audits is not incidental but systemic, and calls for institutional reforms in transparency, supervision, and whistleblower protection. Recommendations for further research include qualitative studies on audit culture and comparative analysis of corruption-prone regions.